Effectiveness of vestibular rehabilitation among post-stroke pusher syndrome - Muniyandi, Varshini; Srinivasan, Vignesh; Suganthirababu, Prathap (International Journal of Research in Medical Sciences, 2025)
Background: Pusher syndrome is a post-stroke neurobehavioral disorder characterized by a distorted perception of upright posture and active pushing toward the hemiparetic side, leading to impaired balance, increased fall risk, and delayed rehabilitation. Methods: This randomized clinical trial included 36 post-stroke patients diagnosed with pusher syndrome. Participants were randomly assigned to two groups for an 8-week intervention, conducted twice weekly with two sessions per day. Group A received vestibular rehabilitation therapy (VRT) focusing on gaze stabilization, dynamic balance, and proprioceptive training. Group B performed trunk and core stability exercises. Outcome measures included the scale for contraversive pushing (SCP) and postural assessment scale for stroke patients (PASS), assessed pre- and post-intervention. Results: Both groups demonstrated significant improvement; however, group A showed a greater reduction in SCP scores (6.09±0.19 to 2.89±0.17, p<0.001) and a greater increase in PASS scores (11.6±1.1 to 25.8±1.0, p<0.001) compared to group B. Between-group analysis confirmed that VRT was significantly more effective in reducing contraversive pushing and improving postural control. Conclusions: VRT is more effective than trunk stability exercises in improving postural alignment, reducing contraversive pushing, and enhancing functional independence in post-stroke pusher syndrome. Incorporating vestibular strategies into stroke rehabilitation may optimize recovery.